A Common Man’s Guide to the Common Market - Arbuthnott, Hugh. author. aut Link
VIII, 236 p.
Keywords: The purpose of this revised and extended book is to try to explain how the policies of the Community are meant to achieve its primary objectives. A short history of the foundation and major events are included and the formal institutions and the actual decision-making processes are explained.